2007
DOI: 10.1158/0008-5472.can-07-0686
|View full text |Cite
|
Sign up to set email alerts
|

IFN-β Signaling Positively Regulates Tumorigenesis in Aggressive Fibromatosis, Potentially by Modulating Mesenchymal Progenitors

Abstract: Aggressive fibromatosis (also called desmoid tumor) is a benign, locally invasive, soft tissue tumor composed of cells with mesenchymal characteristics. These tumors are characterized by increased levels of B-catenin-mediated T-cell factor (TCF)-dependent transcriptional activation. We found that type 1 IFN signaling is activated in human and murine aggressive fibromatosis tumors and that the expression of associated response genes is regulated by B-catenin. When mice deficient for the type 1 IFN receptor (Ifn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
(60 reference statements)
0
18
0
1
Order By: Relevance
“…Partial response has been observed in a patient with temporal fossa [34] and foot [35] fibromatosis. A study showed that IFN signaling is regulated by the β-catenin pathway [36]. IFN-α therapy did not allow tumoral response, which may be explained by experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial response has been observed in a patient with temporal fossa [34] and foot [35] fibromatosis. A study showed that IFN signaling is regulated by the β-catenin pathway [36]. IFN-α therapy did not allow tumoral response, which may be explained by experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tjandra et al, IFN may decrease the proliferation of fibromatosis tumor cells, but do not affect tumoral stem cells, which may increase their proportion in the tumor. These stem cells are resistant to IFN, which could also explain the resistance to treatment [36]. Moreover, IFN-induced asthenia and daily subcutaneous administration may limit treatment observance.…”
Section: Discussionmentioning
confidence: 99%
“…The type I IFN receptor is ubiquitously expressed by host cells, including tumor cells. Intriguingly, a host defect related to type I IFNs or their signaling can result in different cell-type transformations and tumorigenesis (1)(2)(3)(4). In fact, type I IFNs are known to effectively activate DC maturation and are required for the early stage priming of tumor-specific T cells (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, IFNβ directly inhibits tumor growth when secreted by the tumor microenvironment [18]. On the other hand, IFNβ partakes in tumor escape from the immune system, either by selecting for IFN non-responsive cells [19] or by contributing to oncogenic Ras transformation [20] and enriching for cancer initiating cells [21]. Although IFNβ seems to cooperate with wild type p53 in tumor suppression and stress responses [22], [23], [24], its interaction with the mutant forms of p53 has not been investigated.…”
Section: Introductionmentioning
confidence: 99%